1997
DOI: 10.1177/026839629701200406
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Implementing Is: A Case Study Analysis in Social Services

Abstract: Many organizations fail to implement or reap the benefits of information systems (IS) projects. The social care sector is not yet a great user of information technology (IT) and the thinking about IS is generally less well-developed than, for instance, in the health care sector. Research in health informatics indicates that there are special problems in creating integrated solutions and achieving the uptake of systems. This project was therefore undertaken with the benefit of experience of previous projects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Riley and Smith’s ( ) study of IS development and implementation in social services is the first of few studies relating to the use of technology in the social care sector in England. Later studies examined the impact of technology on unskilled work (Munro & Rainbird, ) and the relationship between technology and medical practice (Heath et al, ) and managing mobile provision for community healthcare support (Fitch & Adams, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Riley and Smith’s ( ) study of IS development and implementation in social services is the first of few studies relating to the use of technology in the social care sector in England. Later studies examined the impact of technology on unskilled work (Munro & Rainbird, ) and the relationship between technology and medical practice (Heath et al, ) and managing mobile provision for community healthcare support (Fitch & Adams, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pelletier ( ) identified a lack of IT literacy as a barrier to technology use and Barnard and Gerber ( ) recognized that different skills are required by professionals to use technology. Rhodes ( ) noted that recruitment practice and documentation in the social care did not reflect the importance of IT and information management skills and this may partially explain why Riley and Smith ( ) found that there was a general lack of enthusiasm to use computers within this sector.
H3 : Effort Expectancy will have a significant influence on intention .
…”
Section: Research Context and Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations